Analysis of wall temperature jump of China Generation IV SFR Steam Generator. (April 2018) - Zhong, Xianping; Yu, Jiyang; Yan, Shengyu; Saeed, Muhammad; Li, Yaodong
Highlights: To develop a thermal hydraulic model of sodium-heated once-through steam generator. To analyze the wall temperature jump of China Generation IV SFR Steam Generator. The maximum water wall temperature jump is set to about 30 °C. The sodium inlet temperature should be strictly controlled in real operation. The water inlet mass flow rate should be strictly controlled in real operation. Abstract: This paper presents a thermal-hydraulic model of the sodium-heated once-through steam generator and its application to analyze the wall temperature jump of China Generation IV SFR Steam Generator (CSSG). Firstly, this model is verified with experimental data and another design code, which proves the reliability of this model. Secondly, the heat transfer characteristics of CSSG is obtained by using this model. Thirdly, the location and magnitude of maximum water wall temperature jump are chosen as figures of merit for the sensitivity analysis for CSSG. Based on numerical calculations and conservative consideration, it is concluded that the sodium inlet temperature and the water inlet mass flow rate must be strictly controlled in the operation of CSSG, and that the maximum water wall temperature jump is set to around 30 °C in the following stress design.